2020
DOI: 10.1126/science.aba0210
|View full text |Cite
|
Sign up to set email alerts
|

Intravital imaging of mouse embryos

Abstract: Embryonic development is a complex process that is unamenable to direct observation. In this study, we implanted a window to the mouse uterus to visualize the developing embryo from embryonic day 9.5 to birth. This removable intravital window allowed manipulation and high-resolution imaging. In live mouse embryos, we observed transient neurotransmission and early vascularization of neural crest cell (NCC)–derived perivascular cells in the brain, autophagy in the retina, viral gene delivery, and chemical diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 47 publications
1
62
0
Order By: Relevance
“…We have developed an in vivo lineage tracing strategy based on Cre-loxp system to observe the target cells in living mouse [29]. Similarly, by taking advantage of a transgenic strains with fluorescent reporters and two-photon microscopy, Huang et al recently reported they observed the development of mouse embryos intravitally [30].…”
Section: Discussionmentioning
confidence: 99%
“…We have developed an in vivo lineage tracing strategy based on Cre-loxp system to observe the target cells in living mouse [29]. Similarly, by taking advantage of a transgenic strains with fluorescent reporters and two-photon microscopy, Huang et al recently reported they observed the development of mouse embryos intravitally [30].…”
Section: Discussionmentioning
confidence: 99%
“…This powerful approach is increasingly leveraged in experimental and pre-clinical studies to reveal novel insights into the dynamic cellular mechanisms underlying disease development and response to therapy (4,5). To facilitate repeated IVM over prolonged time periods in the same living animal, multiple imaging windows have been designed to provide optical access to internal tissues (6), including the brain (7), skin (8,9), lung (10), mammary gland (6,11,12), abdominal organs (13)(14)(15), femur (16) and embryos (17).…”
Section: Introductionmentioning
confidence: 99%
“…Intravital imaging, the imaging of live animals at microscopic resolution, is gaining increasing attention in biomedicine because it can provide multicolour spatiotemporal information at single-cell resolution in a variety of organs in vivo . In addition to the early imaging of lymph nodes [ 4 , 5 ] and recent visualization of mouse embryos [6] , intravital imaging has become a critical tool to reveal the novel mechanism of nanoparticle transport in the tumour microenvironment [7] , [8] , [9] . Here, we review recent progress on the use of intravital imaging in answering fundamental questions about nanoparticle delivery in vivo .…”
Section: Introductionmentioning
confidence: 99%